Философия учебное пособие для вузов - Корниенко А. А. Алла Александровна; Квеско Р. Б. Раиса Брониславовна; Макиенко М. А. Марина Алексеевна; Ботьева О. В. Ольга Владиленовна; Брылина И. В. Ирина Владимировна; Гульбин Г. К. Геннадий Константинович; Макаренко Н. И. Наталья Ивановна; Мигуренко Р. А. Раиса Афанасьевна; Рубанова Е. В. Елена Витальевна; Плотников Ю. С. Юрий Семёнович; Фадеева В. Н. Вера Николаевна (Учебники Томского политехнического университета)
Заглавие с титульного экрана